2015
DOI: 10.1016/j.gaceta.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Resultados de un programa de telemedicina para pacientes con diabetes tipo 2 en atención primaria

Abstract: Although glycemic control did not improve during the follow-up, electronic transmission of information was found to be feasible and satisfactory for patients. The patients reported a higher level of self-perceived health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
4
0
3
Order By: Relevance
“…The level of satisfaction with TM that was observed in our study is comparable to that seen in previous studies. In one of these, the level of satisfaction of patients who had participated in TM programmes conducted in six health centres in the Albacete healthcare region, was high or very high in 96% of cases 20. Similarly, another study found that patients’ acceptance was 5.8 (IQR 5.2–6) on a scale from 1 to 6 37…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The level of satisfaction with TM that was observed in our study is comparable to that seen in previous studies. In one of these, the level of satisfaction of patients who had participated in TM programmes conducted in six health centres in the Albacete healthcare region, was high or very high in 96% of cases 20. Similarly, another study found that patients’ acceptance was 5.8 (IQR 5.2–6) on a scale from 1 to 6 37…”
Section: Discussionmentioning
confidence: 95%
“…Thus, patients who use TM have shown a greater reduction of glycated haemoglobin (HbA1c) levels than those receiving usual care 13 14. Moreover, the use of TM, at least in specific interventions, helps to optimise improvement of weight control,15 body mass index,15 blood pressure,16 17 low-density lipoprotein values,17 18 pain19 and to improve health-related quality of life 15 19 20. At the same time, TM is a useful tool for reducing the number of visits to the doctor by patients with T2DM, thereby saving time and money on commutes 21–23…”
Section: Introductionmentioning
confidence: 99%
“…Por fim, o uso de tecnologias para o acompanhamento remoto e a consulta por telessaúde tornaram-se um meio bastante difundido, e não obstante, sabe-se que são estratégias úteis para que as pessoas tenham acesso a orientações para promoção e prevenção em saúde, sobretudo as pessoas que vivem com doenças crônicas como o diabetes (11,(14)(15)21) . No entanto, a utilização de tais recursos exige aceitação dos pacientes, treinamento e disponibilidade dos meios tecnológicos necessários (49) .…”
Section: Características Metodológicas/objetivosunclassified
“…Según Collazos y Torres (2018), Fernández et al (2016), Moreno (2017), López et al (2015) y Medianero y Samamé (2018), la Telemedicina es una práctica para el servicio de la salud a distancia y lugares hostiles y de factor crítico, con el objetivo de intercambiar datos para hacer un diagnóstico, todo esto gracias a la tecnología de la información y la comunicación entre un servicio sanitario y los pacientes, en las que la intervención de diagnóstico y decisiones y recomendaciones de los tratamientos están basados en la trasmisión de información como datos, imágenes, videos, documentos, grabaciones de voz. Todo esto trasmitido a través de sistemas de telecomunicación.…”
Section: La Telemedicinaunclassified